Measuring patient satisfaction with the CT consent process: the COMRADE outcome measure. (December 2013) - Rogers, Patrick; Lloyd, Simon; Shetty, Dushyant; Newell, Paul; Gay, David
There is debate around whether we should be obtaining formal consent from patients prior to them undergoing diagnostic CT examination, and whether this is indeed practical or possible. The debate raises the question: if we were to introduce such a practice, how would we be able to judge that the consent-seeking process was effective in communicating risk and in making the patient feel that they were taking a fully informed decision? We use the Combined Outcome Measure for Risk Communication and treatment Decision making Effectiveness (COMRADE) score to assess levels of patient perception of effective risk communication and confidence in their decision to undergo CT. We evaluate this measure by using it to assess patients attending our center's imaging department for outpatient CT.